ISTILAH-ISTILAH KHUSUS DALAM CHATTING (Sebuah Analisis Sosiopragmatik) - Bambang Hariyanto (Adabiyyāt: Jurnal Bahasa dan Sastra, 2010)
This paper aims at describing the use of language on the internet, especially language terms in chatting. It is claimed that the language terms have an important role for the chatters to make interaction and relationship with each other for certain purposes. The important role of language can be seen from the fact that many chatters use different language styles and speech variations in chatting over the Internet Relay Chat (IRC). The model of IRC communication is a kind of communication media for communication (chatting) by using computer keyboard in writing symbols or "emoticons", and codes (register) in the conversation with other chatters. The writer uses descriptive method combined with socio-pragmatics approach of Grice’s Maxim theories to explain the special terms of language use in chatting. The study was based on the data from 13 speech channels and 10 couples of private speech on mIRC program and YM in Yogyakarta area. Based on the elaboration, the writer has found four criteria of chatting conversation as follows. (1) Chatting has a special term in the use of codes (register) for conveying something to their partners in speaking, such as abbreviations. (2) Chatting has special forms of Emoticon. (3) Chatting has special identity codes and (4) Chatting has special lengthened the words.